(3EJeGe JJeI UhGf GdMceI ddSLRjs - (3eLghds; (3GdSLRjs
(3ChdgG (B:s
(3jLH CHJOGA GdCbhGd , hGaJJJGM GdCMhGd HGSe Gddg GdCYXe aCbhd (B: (3gPg GdQSGdI GdedMbI HcJGH JJeI UhGf GdMceI GdJi hYOJgG ai C hd GdLRA GdeNJUQ ef cJGH UhGf GdMceI EdN s
(3BNQgG (B:s
(3gPG BNQ GdcJGH hGdMeO ddg QH GdYGdejf , hUdi Gddg Ydi QSdg GdeUWajf s
(3JHUQI GdYfhGf (B:s
(3JPjjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B558 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B5 s
(3eUOQ GbJfGA GdCUd (B:s
(3chHQjdi (B(902) s
Keywords: (3GdJGQjNs